ISOLATION OF TOXOPLASMA GONDII FROM HUMAN TISSUES - M. Ghorbani; A. Hafizi; A. Sanati; H. Modarres-Musavi (Tehran University of Medical Sciences, 1979)
Nineteen lymph node biopsies, 3 curetting, 15 blood samples obtained from patients with lymphadenitis and high titers of Toxoplasma antibodies, and 27 tonsillar tissues removed from patients because of chronic tonsillitis were inoculated intraperitoneally into mice for isolation of toxoplasma gondii. Toxoplasms were isolated from 5 lymph node biopsies, one curettage material, 2 tonsillar tissues and none of the blood samples.